Mapping the epidemiology and trends of extra-pulmonary tuberculosis in Saudi Arabia. Issue 4 (December 2015) - Varghese, Bright; Al-Hajoj, Sahal
Abstract: An extra-pulmonary tuberculosis (EPTB) infection rate of 30% in Saudi Arabia remains above the global rate. A variable rate of infection in each province has been reported and the involvement of most organs has been cited. Nationwide collective data on the current trends of infection are scarce and the factors behind the increased rate of EPTB are perplexing. This review endeavors to shed light into the epidemiology of EPTB, various types of infections sites, geographical differences in the infection rate, known risk factors, and challenges in the diagnosis and management of EPTB in Saudi Arabia.